Quantification of Cervical Cord Cross-Sectional Area: Which Acquisition, Vertebra Level, and Analysis Software? A Multicenter Repeatability Study on a Traveling Healthy Volunteer - Lukas, Carsten; Bellenberg, Barbara; Prados, Ferran; Valsasina, Paola; Parmar, Katrin; Brouwer, Iman; Pareto, Deborah; Rovira, Àlex; Sastre-Garriga, Jaume; Gandini Wheeler-Kingshott, Claudia A. M.; Kappos, Ludwig; Rocca, Maria A.; et al. (Frontiers in Neurology, 2021)
Background: Considerable spinal cord (SC) atrophy occurs in multiple sclerosis (MS). While MRI based techniques for SC cross-sectional area (CSA) quantification have improved over time, there is no common agreement on whether to measure at single vertebral levels or across larger regions, and whether upper spinal cord CSA can be reliably measured from brain images. Aim: To compare in a multi-center setting three CSA measurement methods in terms of repeatability at different anatomical levels. To analyze the agreement between measurements performed on cervical cord and on brain MRI. Method: One healthy volunteer was scanned three times on the same day in six sites (three scanner vendors) using a 3T MRI protocol including sagittal 3D-T1 weighted imaging of the brain (covering the upper cervical cord) and of the SC. Images were analyzed using two semi-automated methods (NeuroQlab, NQL and the Active Surface Model, ASM) and the fully automated Spinal Cord Toolbox (SCT) on different vertebral levels: (C1-C2;C2/3) on SC and brain images, and the entire cervical cord (C1-C7) on SC images only. Results: CSA estimates were significantly smaller using SCT compared to NQL and ASM (p <0.001), regardless of the cord level. Inter-scanner repeatability was best in C1-C7: coefficients of variation for NQL, ASM and SCT: 0.4%, 0.6% and 1.0%, respectively. CSA estimated in brain MRI were slightly lower than in SC‐MRI (all p <=0.006 at the C1‐C2 level). Despite protocol harmonization between the centers with regard to image resolution and use of high contrast 3D-T1 weighted sequences, the variability of CSA was partly scanner dependent, probably due to differences in scanner geometry, coil design and details of the MRI parameter settings. Conclusion: For CSA quantification dedicated isotropic SC MRI should be acquired, which yielded best repeatability in the entire cervical cord. In the the upper part of the cervical cord, use of brain MRI scans entailed only a minor loss of CSA repeatability compared to SC MRI. Due to systematic differences between scanners and the CSA quantification software, both should be kept constant within a study. The MRI dataset of this study is available publicly to test new analysis approaches.